STUDI PENERAPAN RNAV-1 DALAM PENINGKATAN KAPASITAS RUANG UDARA APP/TMA PALEMBANG - Rizky Rahmawati; Pangsa Rizkina Aswia; Sri Rahayu Surtiningtyas (Politeknik Penerbangan Indonesia Curug, 2019)
This study aims to determine and obtain the amount of APP / TMA Palembang airspace capacity after RNAV-1 is applied. This research was carried out at the LPPNPI Public Corporation Palembang Branch in March to April 2019. The method used in this research is the quantitative method. Data collection techniques used are structured observations with the results of the data obtained in the form of the amount of traffic and the total workload of ATC for one hour during peak hours, and literature studies that contain data on the calculation of airspace capacity before the application of RNAV-1 and monthly traffic data. The analysis technique used is to use parametric statistics with the SPSS application in the form of a simple linear regression between the amount of traffic and the total workload of ATC to get the results of airspace capacity after the application of RNAV-1. Before the application of RNAV-1 the airspace capacity had been calculated by the ATFM unit with the result that the airspace capacity in one hour was 16 traffic / hour. After research and analysis, after the application of RNAV-1 there was an increase in the amount of airspace APP / TMA Palembang to 18 traffic / hour. The increase in airspace capacity after the application of RNAV-1 is 12.5%. With these results, the application of RNAV-1 needs continuous implementation.